ARCHIVES MANAGEMENT IN MI AL – MUHTADIN, BONEPANTAI DISTRICT, BONE BOLANGO DISTRICT - Friska Piyohu; Imam Mashudi; Risna Sanaba (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This scientific writing report aims to 1. To find out the management of archives at Mi Al–Muhtadin, Bonepantai District, Bone Bolango Regency. 2. To find out the obstacles that arise in the implementation of archive management at Mi Al-Muhtadin, Bonepantai District, Bone Bolango Regency. The report method used is based on a phenomenon that often occurs in the field, namely that archive management in madrasas is generally not implemented properly. Therefore a good archival management system is needed, especially in a document or archive storage system. Through the implementation of good records management, it can indirectly improve the quality of administrative services. The results of this scientific paper report show that the implementation of archive management is carried out by the administrative administration section in managing important documents and archives for madrasas through planning, organizing, implementing, and supervising. Archival planning activities include: Room planning, storage equipment, storage equipment, and storage systems. Archival organizing activities include: Division of duties and responsibilities for archive management, as well as the use of archive storage principles. Archival implementation activities include: procedures for starting archives, storing records, maintaining archives, borrowing archives, and archive depreciation procedures. Archival monitoring activities, through monitoring by the head of the madrasah and the head of the administration section. Quality of administrative administration services using a service system approach and service standards. The results of the implementation of archives management in improving the quality of administrative services at Madrasah Ibtidaiyah Al-Muhtadin, Bonepantai District, Bone Bolango Regency show that administrative administration has carried out archival management functions even though it is not optimal.